Species composition of Ground beetles (Coleoptera: Carabidae) on spring wheat in the Right-Bank Forest-Steppe of Ukraine - Ya. Medvid; N. Havryliuk (Карантин і захист рослин)
Goal. To clarify the species composition of carabids in spring wheat agrocenosis, to determine the dominant species, to compare the number of ground beetles on application of mineral fertilizers and organic nutrients.